Integrating Corporate Social Responsibility into Business Strategy: Creating Sustainable Value - Muhammad Ardiansyah (Involvement International Journal of Business, 2024)
This research aims to explore the integration of Corporate Social Responsibility (CSR) into business strategy and its impact on creating sustainable value. The identified steps in the integration of CSR include defining purpose and values, identifying material issues, setting goals and targets, embedding CSR throughout the organization, engaging stakeholders, integrating CSR into decision-making, measuring and reporting progress, and fostering a culture of continuous improvement. The research highlights significant findings related to the integration of CSR into business strategy. Some key findings include a positive correlation between CSR practices and financial performance, including increased profitability and improved brand reputation. Additionally, integrating CSR can provide advantages in terms of competitive advantage, higher employee engagement, risk mitigation, stakeholder trust, and innovation in product or service development. The challenges that arise in the integration of CSR, such as resource constraints, resistance to change, and the need for effective implementation strategies. In conclusion, this research emphasizes the importance of integrating CSR into business strategy to create sustainable value. By aligning business objectives with social and environmental goals, engaging stakeholders, and continuously improving CSR practices, organizations can contribute to a more sustainable and inclusive future. Moreover, integrating CSR into business strategy can lead to benefits such as improved financial performance, better relationships with stakeholders, and new opportunities for innovation.